Bone, subcutaneous tissue and plasma pharmacokinetics of cefuroxime in total knee replacement patients – a randomized controlled trial comparing continuous and short‐term infusion. Issue 12 (14th October 2019) - Tøttrup, Mikkel; Søballe, Kjeld; Bibby, Bo M.; Hardlei, Tore F.; Hansen, Peter; Fuursted, Kurt; Birke‐Sørensen, Hanne; Bue, Mats
Abstract : Cefuroxime is widely used as antibiotic prophylaxis for orthopaedic procedures. We evaluated bone, subcutaneous tissue (SCT) and plasma pharmacokinetics of cefuroxime in male patients undergoing total knee replacement (TKR) after both traditional short‐term infusion (STI) and continuous infusion (CI). Eighteen male patients undergoing TKR were randomly assigned to STI or CI of 1.5 g of cefuroxime. Measurements were obtained in plasma, SCT, cancellous and cortical bone every 30 min for 8 h following surgery. For sampling in solid tissues, microdialysis was applied. Population pharmacokinetic modelling was performed in order to estimate pharmacokinetic parameters, and to assess the probability of attaining cefuroxime concentrations above clinically relevant minimal inhibitory concentrations (MICs) for 65% and 90% of the 8 h dosing interval. Low SCT and cortical bone penetration were found in both the STI and the CI group, but the findings were only significant in the STI group. Irrespective of MIC, tissue and target, CI leads to improved probability of attaining relevant pharmacokinetic targets compared with STI. For the Staphylococcus aureus MIC breakpoint (4 μg/mL), STI leads to inadequate probability of target attainment. CI of 1.5 g of cefuroxime leads to improved probability of attaining relevant pharmacokinetic targets in male TKR patients compared with traditional STI. These findings suggest that application of CI may improve antibiotic prophylaxis for male TKR patients.